Leadership Education Schools in Minahasa District - Sumual, Herry; Sumual, Tinneke E. M.; Kambu, Kornelius; Paat, Wensi R. L.; Rattu, Olviane I. (International Journal of Information Technology and Education, 2024)
Educational leadership is the ability to influence, coordinate, and mobilize other people who are related to the implementation and development of education so that educational goals can be achieved for schools effectively and efficiently. So that school goals can be achieved effectively and efficiency requires effective school principal leadership. There are seven characteristics of Effective school principal leadership: (1) has a clear vision, (2) has the hope to perform; (3) program And giving bait come back Which is positive And constructive, (4) push utilization time in a way efficient, (5) utilize various learning resources, (6), monitoring student progress both individually nor group, (7), do evaluation And repair in a way sustainable.